Reliability testing of self-care of heart failure index V6.2 Chinese instrument among heart failure patients - Tan, Adam Jian Yang (Tanjung Malim, 2021)
Reliability testing of self-care of heart failure index V6.2 Chinese instrument among heart failure patients by Tan, Adam Jian Yang